Dielectric Properties of 0.95 (Pb𝟏−𝟑𝑥/𝟐La𝑥Zr𝟎.𝟔𝟓Ti𝟎.𝟑𝟓O𝟑)-0.05(Ni𝟎.𝟖Zn𝟎.𝟐Fe𝟐O𝟒) Composites - Rekha Rani; Parveen Kumar; J. K. Juneja; K. K. Raina; Chandra Prakash (Advances in Condensed Matter Physics)
We report studies on dielectric properties of magnetoelectric composites of La-substituted lead zirconate titanate (PLZT) and zinc-doped nickel ferrite (NZF) with compositional formula 0.95 Pb1-3x/2LaxZr0.65Ti0.35O3-0.05 Ni0.8Zn0.2Fe2O4 (𝑥=0, 0.01, 0.02, and 0.03). The materials were synthesized by conventional solid state reaction route. The presence of individual phases (PLZT and NZF) was confirmed by using X-ray diffraction technique. Dielectric properties were studied as a function of temperature and frequency. Significant improvement was observed in dielectric properties with addition of La.